BIOCHEMICAL AND HISTOLOGICAL STUDIES ON ADVERSE EFFECTS OF DIETARY WEIGHT LOSS SUPPLEMENT ON FEMALE RATS: ADIOS - Mohammed , Noor A. (Science Journal of University of Zakho, 2024)
Herbal and dietary supplements are commonly used throughout the world; these unlicensed supplements are not recommended due to concerns about their clinical efficacy and safety. Adios are marketed for weight loss in Iraq and many other countries and are commonly used by women. The safety of these weight loss aids is unknown. This study aimed to evaluate adios adverse effects by conducting biochemical, hematological, and histological examinations on the liver and kidney. Rats were orally administrated for 30 days with different concentrations of adios supplements (0.001g/100g), (0.002g/100g), and (0.003g/100g) as low (LD) medium (MD) and high (HD) concentrations, respectively. The results showed no weight loss in rats over 30 days across experiments in all the treated groups (LD, MD, and HD) compared to the control. Adios showed significant differences between the control and the treated concentrations in the following hematological parameters: white blood cells (WBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), lymphocyte (LYM), and red cell distribution width (RDW) in a dose-dependent pattern. Furthermore, there were various alteration in the histopathological examination of the kidney and liver. From the current data, it can be concluded that adios has zero efficacy in weight loss and is not recommended for use because it has adverse effects on many hematological and biochemical parameters and with obvious pathological changes in both the kidney and liver.